2013
DOI: 10.1002/wrcr.20214
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the spatial variability of water fluxes at the groundwater‐surface water interface

Abstract: [1] There is widespread recognition that the groundwater-surface water interface can have significant influence on the pattern and form of the transfer of nutrient-rich groundwater to rivers. Characterizing and quantifying this influence is critical for successful management of water resources in many catchments, particularly those threatened by rising nitrate levels in groundwater. Building on previous experimental investigations in one such catchment: the River Leith, UK, we report on a multimeasurement, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
109
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(123 citation statements)
references
References 49 publications
14
109
0
Order By: Relevance
“…Particle size sieving of a sediment core collected from the thalweg of the river in the UVS revealed that about 50 % of the overlying sediments mainly consisted of gravels ([2 and \63 mm) in the upper 40 cm Binley et al 2013), which is consistent with Krause et al (2009). DET probes fabricated into 30 cm long plastic plates and protected in stainless steel holders were deployed into the river bed for four occasions between July and September 2010 coinciding with the main plant growth season.…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…Particle size sieving of a sediment core collected from the thalweg of the river in the UVS revealed that about 50 % of the overlying sediments mainly consisted of gravels ([2 and \63 mm) in the upper 40 cm Binley et al 2013), which is consistent with Krause et al (2009). DET probes fabricated into 30 cm long plastic plates and protected in stainless steel holders were deployed into the river bed for four occasions between July and September 2010 coinciding with the main plant growth season.…”
Section: Methodsmentioning
confidence: 82%
“…Dissimilatory nitrate reduction to ammonium (DNRA) could be an additional sink for pore water nitrate loss beneath VS (Kelso et al 1997); however, the potential for NO 3 -loss through DNRA was of minimal importance compared to denitrification in the un-vegetated sediments of River Leith . That said, dilution of pore water NO 3 -by down-welling surface water (with lower NO 3 -levels than the upwelling groundwater) may have been another possibility for the observed low NO 3 -under VS; however, the likelihood of significant dilution effect particularly in sediments deeper than 10 cm appear minor given the fact that the river is predominantly groundwater-fed under base flow conditions (Kaeser et al 2009;Binley et al 2013). ?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations